TINJAUAN PEMANFAATAN LIMBAH KULIT JAGUNG PADA PRODUK FASHION - Agustina Dwi Lestari (Universitas Mercu Buana, 2021)
Based on the survey, there are already many fashions that use corn husk waste processing materials. Therefore, this research focuses on the waste processing techniques of corn husk for fashion. This study used an explanative qualitative method to analyze the processing of corn husk waste for fashion products. The processing of corn husk waste is done through the raft engineering technique by going through several stages, namely using the initial exploration-making stage which is used by applying the twisted, twisted, twisted twine, twisting, dense twisting, and crochet crafting technique. This weaving weave is composed by applying it using the raft technique of yarn, twisting, twisting twice, loosely twisting, dense twisting, and crochet, because to produce an attractive texture and get different results from the others, the last exploration stage is the technique. assemble thread rafts by applying using the twisted, twisted, twisted, loose twisted, dense twisting and crochet crafting technique. Meanwhile, in the process of coloring the results of the raft technique with the experimental method through a process of several stages in the form of a pickling process with bleaching and scouring techniques, the coloring process with natural colors that come from nature, the cutting process, and the forming process with the weaving technique using yarn in the union.